Governor Herman Deru Leadership Style in the Implementation of the Regional Government System for the 2018-2023 Period in South Sumatra Province - Mahriadi, Nopriawan; Akib, Haedar; Sailan, Manan (International Journal of Humanities, Education, and Social Sciences, 2025)
Leaders are the main agents of change. PP No. 33 of 2018 The governor is the representative of the central government in the region, his duty is to oversee the provincial regulations The governor has the task of coordinating, monitoring, evaluating, and supervising the implementation of local government. The research method uses a qualitative approach to the research object of the Governor of South Sumatra collecting data observation interviews documentation, conducted to regents and mayors in South Sumatra using Robert House's path goal theory analysis derective, supportive, participative and achievement oriented. As well as presenting data in qualitative case studies. The results showed that of the four aspects of the leadership style of the path goal theory, there are three aspects that have generally gone well including, in the derective leadership aspect, in the supportive leadership aspect and in the achievement oriented leadership aspect, all of these aspects are optimal. However, in the participative leadership aspect, it is not optimal for the special allocation funds that have been disbursed as much as IDR 3.9 trillion, there are BPK RI findings on the realization of the distribution of special funds for governor assistance that do not have standardized standards in their distribution. the dominant determinant factor is the supportive leadership factor Herman Deru's attitude brings the work atmosphere to feel more fun, the popilarity factor, the communication factor and the development factor.